2015
DOI: 10.7314/apjcp.2015.16.9.3729
|View full text |Cite
|
Sign up to set email alerts
|

Personal and Socio-Cultural Barriers to Cervical Cancer Screening in Iran, Patient and Provider Perceptions: a Qualitative Study

Abstract: Background: Although cervical cancer is preventable and early screening might decrease the associated mortality, challenges faced by the women and health care providers can postpone early detection. This qualitative study aimed to establish patient and provider perceptions about personal and socio-cultural barriers for cervical cancer screening in Mashhad, Iran. Materials and Methods: In the present study, which was conducted in 2012, eighteen participants, who were selected purposefully, participated in indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 22 publications
1
30
0
1
Order By: Relevance
“…Moreover, the participation rates in rural areas might be more affected by under-reporting due to embarrassment in admitting to have been screened for cervical cancer than in urban settings, where negative beliefs associated with the disease is less common. [15] This study also revealed evidence of disparities in cervical cancer screening participation across socio-economic groups in Iran. Contradicting with ndings in most countries, women with higher socio-economic status had shown lower participation in cervical cancer screening program.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Moreover, the participation rates in rural areas might be more affected by under-reporting due to embarrassment in admitting to have been screened for cervical cancer than in urban settings, where negative beliefs associated with the disease is less common. [15] This study also revealed evidence of disparities in cervical cancer screening participation across socio-economic groups in Iran. Contradicting with ndings in most countries, women with higher socio-economic status had shown lower participation in cervical cancer screening program.…”
Section: Discussionmentioning
confidence: 54%
“…[12,13] Existing literature has highlighted factors like age, marital status, embarrassment, lack of knowledge, and socio-cultural beliefs around cervical cancer as the main causes of nonattendance in cervical cancer screening program in Iran. [14,15] However, despite the global growing concern about health equity in recent decades, there are limited studies examining regional and socio-economic variations in cervical cancer screening uptake in the country. Hence, this study sought to assess the disparities in cervical cancer screening participation in Iran according to the data obtained from the National Survey of The Risk Factors of Non-Communicable Diseases (STEPs 2016), and to identify socio-demographic factors that predict the participation in cervical cancer screening program.…”
Section: Introductionmentioning
confidence: 99%
“…While direct comparisons with other studies are not possible due to differences in design and study population, this is somewhat lower than results previously reported in Iran. In qualitative studies, Iranian women did not attend cervical cancer screening , and breast cancer patients delayed seeking treatment because they believed it was impossible to treat cancer. Moreover, a study evaluating Iranian women's beliefs about breast cancer showed that many of them considered the disease incurable .…”
Section: Discussionmentioning
confidence: 99%
“…Studies across the world have shown socio cultural hurdles in cervical cancer screening programs. [26,27] Socio cultural factors do play a role in community based activities in India also. These women were allowed to attend because the volunteers had promised them that the test would be done by lady doctors.…”
Section: Discussionmentioning
confidence: 99%